The transferability of Open Reusable Learning Objects (RLOs) to nursing clinical skills education in the Saudi context: a mixed method study - Lamphon, Hadeel (2020)
Background: A key challenge in nursing education now, in light of the ongoing ‘fitness to practise’ debate, is to make nursing clinical skills education (CSE) suitable, accessible, available, and smart for a larger student cohort. Web-based/online learning technology has gained popularity in supporting nursing clinical skills education in an era of rapid expansion of technology. However, the development of these e-learning interventions needs financial and human investment. With the ease of uploading material to the internet, recent years have seen a rapid increase in the development and use of Open Educational Resources (OERs) globally. Nevertheless, the spread of OERs to many countries is delayed for reasons such as cultural, social, and legal factors. While there is potential to use existing resources of this kind in the form of OERs, there is no evidence as to how these may transfer to another setting in nursing CSE. Reusable Learning Objects (RLOs) are one form of OERs and the focus of this study.